Enabling OpenAthens Single Sign On (SSO) Remote Access Authentication to eResources: A Case Study - M, Mohan Tej; Rao, Mahabaleshwara; K, Shivananda Bhat (DESIDOC Journal of Library & Information Technology, 2023)
Accessing the library’s subscribed electronic resources remotely by users has always been a challenge for the library. KMC Health Sciences Library, Manipal relied on proxy-based authentication to remotely cater its e-resources to library users. To enhance the secure usage of electronic resources and to provide user-friendly authentication, the library has considered a Single Sign-On (SSO) remote access through OpenAthens. The article demonstrates the setup process of OpenAthens and the various steps involved in the transformation of the library from proxy-based authentication. The single sign-on setup at the library has benefited users in having a single set of credentials to access all the library e-resources, reducing the hassle of remembering multiple login credentials. Features such as cloud hosting, granular usage reports, and the admin dashboard gave complete hold on the usage of library e-resources. Although OpenAthens has its merits, the setup process involved challenges in the integration of existing library-subscribed e-resources. This article provides insight into the step-by-step process of enabling OpenAthens, addresses troubleshooters, and makes recommendations to libraries looking towards SSO remote access.